Pengaruh Komitmen Organisasi Dan Kompetensi Terhadap Kepuasan Kerja Karyawan Pada Fakultas Teknik Universitas Syiah Kuala - Lukman T.Ibrahim; Yuliana Yuliana; Darnelly Darnelly; Haswinda Pratiwi (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2021)
Abstract: This study aims to determine the effect of organizational commitment and competence on employee job satisfaction at the Faculty of Engineering, University of Syiah Kuala. The population in this study were employees of the Faculty of Engineering, Syiah Kuala University. The number of ASN in the Faculty of Engineering is 50 people. Data collection techniques are methods used to obtain data and information needed in research. Data collection techniques in this study are expected to provide accurate and more specific data, the technique used in this study is to use a questionnaire. The organizational commitment variable (X1) has a strong relationship with job satisfaction (Y) of employees at the Faculty of Engineering Unsyiah with a tcount of 3.251, while a t-table value of 1.677. While the job competency variable (X2) has an effect on job satisfaction (Y) as evidenced by the t-count value of 2.744, while the t-table value is 1.677.